THE EFFECT OF INTEREST RATES CHARGES ON ECONOMIC GROWTH IN TANZANIA, A CASE OF ILALA MUNICIPAL - Halipha Iddy Mnunka; Masese Fred (ZILLZELL MEDIA PRIMA, 2025)
Globally, interest rates have fallen to extreme lows in advanced economies and are expected to remain low. At the same time, market concentration, corporate profits and profit markups are constantly increasing. Additionally, the productivity gap between leaders and followers within the same industry has widened. The study aimed to investigate the effect of interest rates charges on economic growth in Tanzania. The study adopted case study research design with quantitative approach. The study adopted probability sampling procedure. The study used Slovenes formula to obtain sample size of 378 from target population of 6893 respondents. The study used questionnaire to obtain data needed. The finding of the study indicates that interest rate led to increase price of commodities in the market indicates that, Changes in interest rates can also affect the broader economy, influencing consumer behavior and demand for commodities. Higher rates can slow economic growth, leading to reduced demand for certain commodities. Also, interest rates affect currency values. Higher rates can lead to a stronger domestic currency... The study concluded that higher interest rates can drive up commodity prices and influence consumer behavior, potentially slowing economic growth and reducing demand for certain goods. This demonstrates that fluctuations in interest rates have broader implications for the economy. Also, increased interest rates can strengthen the domestic currency, but this appreciation may make commodities more expensive for foreign buyers, further complicating demand dynamics.